2021
DOI: 10.5334/bc.76
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned from 20 years of CBE’s occupant surveys

Abstract: Buildings influence diverse factors (e.g. health, wellbeing, productivity, and social connection). Occupants' direct experiences with their indoor environments allow them to determine whether those spaces support or hinder the activities performed. However, most post-occupancy evaluations (POEs) focus solely on measuring people's levels of comfort and environmental satisfaction. With increasing attention and interest in occupant health and wellness, there is a need to reassess whether occupant surveys are eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 32 publications
2
46
1
Order By: Relevance
“…In other words, buildings can potentially affect occupants' health, wellbeing, productivity, and social connection, and thereby surveying occupants' opinions about whether or not the indoor environment supports the activities performed is imperative. However, most postoccupancy evaluations have concentrated mainly on measuring residents' levels of comfort and environmental satisfaction, and adequate attention has not been paid to their social wellbeing [17]. It is worth mentioning that social interactions, both in terms of quality and quantity, can have a short-and long-term influence on occupants' mental wellbeing and physical health [18].…”
Section: Introductionmentioning
confidence: 99%
“…In other words, buildings can potentially affect occupants' health, wellbeing, productivity, and social connection, and thereby surveying occupants' opinions about whether or not the indoor environment supports the activities performed is imperative. However, most postoccupancy evaluations have concentrated mainly on measuring residents' levels of comfort and environmental satisfaction, and adequate attention has not been paid to their social wellbeing [17]. It is worth mentioning that social interactions, both in terms of quality and quantity, can have a short-and long-term influence on occupants' mental wellbeing and physical health [18].…”
Section: Introductionmentioning
confidence: 99%
“…A mixed-methods, multi-phased approach was used for the evaluation, revision, and validation of the survey instrument. Early survey item development was based on a review of existing post occupancy surveys in healthcare settings, and leaned particularly on the Center for the Built Environment Occupant Toolkit [ 48 , 49 ]. Survey items underwent further iteration in response to research questions explored, and gaps identified, in the literature examining clinical caregivers’ relationship to the healthcare built environment [ 50 , 51 ].…”
Section: Methodsmentioning
confidence: 99%
“…This study relied on occupant satisfaction data collected by the Center for the Built Environment (CBE) at the University of California, Berkeley [ 17 , 18 ]. The IEQ occupant satisfaction survey covers nine core categories including thermal comfort and acoustics [ 19 ].…”
Section: Methodsmentioning
confidence: 99%